Influence of bean seed density on germination and plant vigor - Cunha, João Marcos da; Godoy, Oswaldo Pereira; Ramalho, Magno António Patto; Fernandes, Denise Cunha (Pesquisa Agropecuaria Brasileira, 2014)
Bean (Phaseolus vulgaris L.) ‘Rico 23' seeds were separated into four classes according to their density using sucrose solutions of 1,225, 1,250, 1,275, 1,300 and 1.325 densities. Seeds of the four density classes and those of the unselected (control treatment) were planted in sandy soil. The objective was to determine the vigor through number and speed of emerged plants, weight of aerial parts of dry plants and productivity of plants. The results of the analyses carried out under the prevailing conditions led to the following conclusion: seeds with densities above 1.215 are more vigorous since they presented higher germination capacity, more rapid emergence, and originated more vigorous plants and of higher productivity.